2021
DOI: 10.3390/nu13124368
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Activity of Coffee Brew Evaluated after Simulated Gastrointestinal Digestion

Abstract: Coffee contains human health-related molecules, namely polyphenols that possess a wide range of pharmacological functions, and their intake is associated with reduced colon cancer risk. This study aimed to assess the changes in the anti-inflammatory and antioxidant activity of coffee after simulated gastrointestinal digestion. The evaluation of intracellular reactive oxygen species (ROS) levels in the HT-29 human colon cancer cell line and three in vitro spectrophotometric assays were performed to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Among the individual phenolic compounds, 3- O -caffeoylquinic and 5- O -caffeoylquinic acids were the most prevalent hydroxycinnamic acids detected, accounting for 28.7% and 27.5% of the total phenolic compounds, respectively. The reported data agree with previous studies suggesting that 3- O -caffeoylquinic and 5- O -caffeoylquinic acids accounted for the highest proportion of total phenolic compounds observed in various coffees [ 33 , 45 , 46 , 47 ]. On the contrary, di-caffeoylquinic acids are less soluble than caffeoylquinic acids; hence, they are released more slowly during water extraction [ 48 ].…”
Section: Resultssupporting
confidence: 92%
“…Among the individual phenolic compounds, 3- O -caffeoylquinic and 5- O -caffeoylquinic acids were the most prevalent hydroxycinnamic acids detected, accounting for 28.7% and 27.5% of the total phenolic compounds, respectively. The reported data agree with previous studies suggesting that 3- O -caffeoylquinic and 5- O -caffeoylquinic acids accounted for the highest proportion of total phenolic compounds observed in various coffees [ 33 , 45 , 46 , 47 ]. On the contrary, di-caffeoylquinic acids are less soluble than caffeoylquinic acids; hence, they are released more slowly during water extraction [ 48 ].…”
Section: Resultssupporting
confidence: 92%
“…In addition, digestion in the gastrointestinal tract affects the activities of coffee biocomponents, particularly polyphenols [ 57 ]. Studies have confirmed that the CGA content in coffee increases after digestion [ 58 ], which might enhance the anti-inflammatory effects of coffee.…”
Section: Discussionmentioning
confidence: 98%
“…Pronase E is made up of bacterial proteases, while Viscozyme L is an enzyme complex of different carbohydrases, including β-glucanase, hemicellulase, arabanase, xylanase, and cellulase. Although it is recognized that protocols that use fecal inoculum to study colon digestion are the most accurate in mimicking microbiota activity [ 51 ], a growing number of studies have proposed the use of Pronase E and Viscozyme L as a valid alternative to reproduce the intestinal microbiota activity [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%